Romanticism Redux: The Triumph of the Allman Brothers Band - Gracyk, Theodore (Scenari, 2021)
The Allman Brothers Band is surprisingly neglected in academic scholarship. In this essay I argue that the band was, from 1969 to 1975, a paradigm case of Romanticism in rock. To this end I advance three arguments. First, by rejecting a teleological model of music’s history, we can defuse Adorno’s criticism that their deployment of Romantic musical strategies is merely a recycling of earlier achievements. By emphasizing their improvisatory performance practice, we can defuse the idea that they set out to create autonomous art. Second, classification as twentieth-century Romantics does not involve an appeal to necessary or sufficient conditions for Romanticism. Instead, it is established by reference to a cluster concept analysis of Romanticism. Third, the improvisational project that was the Allman Brothers Band combined well-established Romantic tropes with the quintessential Romantic musical genre, the fantasy, in which conventional musical elements can contribute to unconventional music. Although rooted in simple and familiar material, Allman Brothers improvisations retained a spontaneous expressivity, especially for an audience unfamiliar with their historical precedents. Together, these features result in musical performances that were, like most jazz, resistive to musical convention in a manner that communicated resistance to prevailing social norms.